Midwives’ Experiences of Caring for Ukrainian War Refugees: A Qualitative Study - Leoniuk K; Sobczak K; Kamińska-Skrzyńska W; Janaszczyk A (Risk Management and Healthcare Policy, 2025)
Katarzyna Leoniuk, Krzysztof Sobczak, Weronika Kamińska-Skrzyńska, Agata Janaszczyk Department of Sociology of Medicine and Medical Communication, Medical University of Gdansk, Gdansk, PolandCorrespondence: Krzysztof Sobczak, Department of Sociology of Medicine and Medical Communication, Medical University of Gdansk, M. Sklodowskiej-Curie 3a Street, Gdansk, Poland, Tel +48 58 349 15 50, Email krzysztof.sobczak@gumed.edu.plPurpose: The outbreak of the war in Ukraine resulted in an increased number of war refugees giving birth in Polish hospitals. The aim of the study was to analyze the experiences of midwives providing perinatal care to war refugees. Additionally, the study aimed to design systemic recommendations to improve the quality of intercultural care.Patients and Methods: The research was conducted using the qualitative method with the online Semi-Structured Interview technique. When structuring the data, the COREQ standard was chosen in accordance with EQUATOR recommendations. The analysis included interviews with 16 professionally active midwives providing perinatal care in Polish hospitals.Results: In the study, midwives indicated four types of barriers in the care of war refugees from Ukraine. These includes: language barriers (n=16), cultural barriers (n=8), educational barriers (n=5) and psychological barriers (n=3). Fifteen respondents indicated the occurrence of differences in the care of Ukrainian women giving birth. The dissimilarities were related to the level of cultural differences (tradition; n=15), differences in accommodation (withdrawal, passivity, alienation; n=15) and in assimilation (instrumental acculturation, informational reorientation; n=11).Conclusion: The obstetric staff notices differences in care, and identifies barriers that affect the quality of medical services provided to war refugees. The analysis of midwives’ statements contributed to the creation of a theoretical concept – a differences in care pyramid. Development of a systemic solution that minimizes the effects of the language barrier is crucial. Moreover, it is important to implement information actions that raise the level of knowledge about the functioning of the health care system in Poland, and prenatal education dedicated to war refugees.Keywords: pregnancy, female, midwifery, refugees, Ukraine, prenatal care